Advertising and children: an older’s matter - Mendiola Vargas, Cecilia (2013)
The promulgation of the Act N° 30021 of Promoting Healthy Eating in Children and Teenagers (Promoción de la Alimentación Saludable para Niños y Adolescentes) has place againon the public agenda the discussion on the regulation of advertising for children, how to do it and how far a State can intervene in issues related to feeding.  This article shows several researches and investigations in different countries which will help to put into perspective the issue.